3LPS-binding protein and its interactions with P. gingivalis LPS modulate pro-inflammatory response and Toll-like receptor signaling in human oral keratinocytes. - Pei-Hui Ding; Richard P Darveau; Cun-Yu Wang; Lijian Jin (PLoS ONE, 2017)
Lipopolysaccharide (LPS)-binding protein (LBP) as an acute-phase protein plays a crucial role in innate host response to bacterial challenge. Our previous study shows that LBP expression in human gingiva is associated with periodontal status. Porphyromonas gingivalis is a keystone periodontopathogen, and its LPS with lipid A structural heterogeneity critically accounts for periodontal pathogenesis. This study investigated the effects of LBP and its interactions with two featured isoforms of P. gingivalis LPS (tetra-acylated LPS1435/1449 and penta-acylated LPS1690) on the expression of pro-inflammatory cytokines in human oral keratinocytes (HOKs), and the involvement of Toll-like receptor (TLR) signaling. HOKs were pre-incubated with recombinant human LBP (rhLBP) at 10ng/ml, 100ng/ml and 1μg/ml for 1 h, followed by the treatment of P. gingivalis LPS1690 or LPS1435/1449 for 3h or 24h respectively. The expression of IL-6 and IL-8, and involvements of TLR2 and TLR4 were analyzed. The genes associated with TLR signaling were assessed by PCR array. Interestingly, rhLBP per se significantly up-regulated the expression of IL-6 and IL-8 in HOKs (p<0.05), which was blocked by TLR2 antibody (p<0.001). LPS1435/1449 down-regulated more significantly rhLBP-induced IL-6 and IL-8 mRNAs with reference to P. gingivalis LPS1690 (approximately 80% vs. 40%, p<0.05; and 90% vs. 36%, p<0.001, respectively). Moreover, rhLBP markedly down-regulated the gene expression of TLRs and their adaptors such as CD180 (-2.44 folds) and MD-1 (-9.62 folds), while the interaction of P. gingivalis LPS1435/1449 with rhLBP greatly up-regulated both transcripts (7.11 and 4.05 folds, respectively). Notably, P. gingivalis LPS1690-rhLBP interaction dramatically up-regulated CD180 transcript (20.86 folds) and significantly down-regulated MD-1 transcript (-6.93 folds). This pioneering study shows that rhLBP enables to enhance the expression of pro-inflammatory cytokines in HOKs through TLR2 signaling pathway. P. gingivalis LPS with different lipid A structures down-regulates to different extents rhLBP-induced cytokine expression, possibly through fine-tuning of the CD180-MD1 complex and relevant TLRs.